Small but mighty: Functional landscape of the versatile geminivirus-encoded C4 protein. - Laura Medina-Puche (Public Library of Science (PLoS), 2021)
The fast-paced evolution of viruses enables them to quickly adapt to the organisms they infect by constantly exploring the potential functional landscape of the proteins encoded in their genomes. Geminiviruses, DNA viruses infecting plants and causing devastating crop diseases worldwide, produce a limited number of multifunctional proteins that mediate the manipulation of the cellular environment to the virus' advantage. Among the proteins produced by the members of this family, C4, the smallest one described to date, is emerging as a powerful viral effector with unexpected versatility. C4 is the only geminiviral protein consistently subjected to positive selection and displays a number of dynamic subcellular localizations, interacting partners, and functions, which can vary between viral species. In this review, we aim to summarize our current knowledge on this remarkable viral protein, encompassing the different aspects of its multilayered diversity, and discuss what it can teach us about geminivirus evolution, invasion requirements, and virulence strategies.